"The Wings of the Cloud Color" by Dara Korniy and Tala Vladimirova: The Problems of the tradition and innovation in the novel (Literatures of the World: Poetics, Mentality and Spirituality, 2015)
In this article the prevailing of the traditional paradigm signs in the novel «The Wings of Colour of Clouds» by Dara Korniy and Tala Vladmyrova is proved. The system kinship of the novel with the foreign analogues of the city fantasy on the image, the motif-plot and the mythopoetic levels is accented. The general tendencies of development of the Ukrainian fantasy prose and Dara Korniy’s novels roll-call are confirmed.
Keywords: tradition; innovation; fantasy; plot; typology; intertextuality; resemblance; system organization